2021
DOI: 10.1111/jocd.14374
|View full text |Cite
|
Sign up to set email alerts
|

The mobility of the superficial and deep midfacial fat compartments: An ultrasound‐based investigation

Abstract: Background: Understanding the mobility of the midface and the separate contributions of the superficial and deep fat compartments is essential for natural esthetic outcomes following soft tissue filler or fat grafting procedures. A study was designed that used ultrasound imaging to demonstrate in vivo visualization and quantification of distances and movements in the midface. Methods: A total of 48 midfaces of 24 healthy Caucasian volunteers, all naïve of esthetic procedures, (22 females; 46.85 (9.8) years; 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Based on Cotofona's findings, it seems that the superficial plane of the lower forehead should be avoided due to the unpredictable and inconsistent presence of the central and paracentral arteries 23 . Another practical fact is that a deep supraperiosteal approach should be favored when augmenting the deep midfacial fat compartments 24 . Lastly, it has been shown that in contrast to current concepts, the angular artery is not located strictly subdermal to the nasolabial sulcus but at a variable depth and in 100% of the investigated cases lateral to the nasolabial sulcus.…”
Section: Ultrasound In Cosmetic Dermatology: Why?mentioning
confidence: 99%
“…Based on Cotofona's findings, it seems that the superficial plane of the lower forehead should be avoided due to the unpredictable and inconsistent presence of the central and paracentral arteries 23 . Another practical fact is that a deep supraperiosteal approach should be favored when augmenting the deep midfacial fat compartments 24 . Lastly, it has been shown that in contrast to current concepts, the angular artery is not located strictly subdermal to the nasolabial sulcus but at a variable depth and in 100% of the investigated cases lateral to the nasolabial sulcus.…”
Section: Ultrasound In Cosmetic Dermatology: Why?mentioning
confidence: 99%
“…Interestingly, a recent ultrasound imaging-based study revealed that the mobility of the deep facial fat compartments is significantly reduced when compared to the mobility of the superficial fat compartments, most probably due to their connection to stable and immobile deep facial structures like nerves and ligaments. 9 The superficial fat compartments, on the contrary, display significant movement during facial animation which explains the formation of apple cheeks in conjunction with the transverse facial septum. 10 Injectors, therefore, favor treating deep facial structures when trying to restructure and recontour the midface or when trying to provide structural support for overlying soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This segmented, overfilled look can be avoided by injecting small amounts of filler and asking the patient to smile periodically between intermittent injections 23 . Deeper injections can also prevent this effect, as the deeper fat compartments are less mobile than more superficial compartments 24 …”
Section: Resultsmentioning
confidence: 99%